Pendampingan Pencarian Research Gap dan Penggunaan Mendeley bagi Dosen di Perguruan Tinggi - Poerwanto, Bobby; Hidayat, Rahmat; Isma, Andika (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
The aim of this activity is to increase the knowledge of STIKES Fatima Pare-Pare lecturers and students in finding research gaps in reputable journal literature, and improve their skills in using Mendeley as a reference management tool. This activity was attended by 27 people from lecturers and students. The method for implementing this activity starts from observation, identifying needs, training, mentoring, and monitoring and evaluation. The result of this activity is an increase in knowledge and skills on the topics covered. In addition, around 70% of participants felt that their knowledge and skills had increased significantly. This means that the activities carried out have an impact on the participants so that after the resource person leaves the activity location there is knowledge sharing between participants so that participants who have not improved much can also understand and implement the material that has been given. It is hoped that this improvement in skills will help lecturers and students in preparing research proposals for funding assistance proposals such as DRTPM research grants, student PKM grants, PPK Ormawa, P2MW, or student final project proposals. This activity led the lecturers to find the research gap better and made it easier to explain the novelty.